The role of galaxy mass on AGN emission: a view from the VANDELS survey. Issue 3 (12th February 2020) - Magliocchetti, M; Pentericci, L; Cirasuolo, M; Zamorani, G; Amorin, R; Bongiorno, A; Cimatti, A; Fontana, A; Garilli, B; Gargiulo, A; Hathi, N P; McLeod, D J; et al.
ABSTRACT: We present a comparative analysis of the properties of active galactic nuclei (AGNs) emitting at radio and X-ray wavelengths. The study is performed on 907 X-ray AGNs and 100 radio AGNs selected on the CDFS and UDS fields and makes use of new and ancillary data available to the VANDELS collaboration. Our results indicate that the mass of the host galaxy is a fundamental quantity that determines the level of AGN activity at the various wavelengths. Indeed, large stellar masses are found to be connected with AGN radio emission, as virtually all radio-active AGNs reside within galaxies of M * > 10 10 M⊙ . Large stellar masses also seem to favour AGN activity in the X-ray, even though X-ray AGNs present a mass distribution that is more spread out and with a non-negligible tail at M * ≲ 10 9 M⊙ . Stellar mass alone is also observed to play a fundamental role in simultaneous radio and X-ray emission: the percentage of AGNs active at both wavelengths increases from around 1 per cent of all X-ray AGNs residing within hosts of M * < 10 11 M⊙ to ∼13 per cent in more massive galaxies. In the case of radio-selected AGNs, such a percentage moves from ∼15 per cent to ∼45 per cent (but up to ∼80 per cent in the deepest fields). Neither cosmic epoch, nor radio luminosity, X-ray luminosity, Eddington ratio or star formation rate of the hosts are found to be connected to an enhanced probability for joint radio + X-ray emission of AGN origin. Furthermore, only a loose relation is observed between X-ray and radio luminosity in those AGNs that are simultaneously active at both frequencies.